Automated Monitoring and Control of Public Street Lighting [PSL] with Placement Strategy Using LoRa-Based Web System - Faridatun Nadziroh; Haniah Mahmudah; Rahardhita Widyatra Subdibyo; Iwan Kurnianto Wibowo; Lucky Pradigta S.R.; Muarifin; Aries Pratiarso; Tri Budi Santoso (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2025)
Public Street Lighting (PSL) is essential for road safety at night. A common issue is the lack of routine inspections, leading to potential hazards. Most maintenance still relies on manual on-site visits. This study proposes an automated PSL system using Long-Range (LoRa) communication and a web-based platform to enhance efficiency and monitoring. The system enables optimized brightness control and scheduling, conserving energy and reducing environmental impact. Real-time monitoring and cloud-based data storage allow remote management via a centralized control system. Motion detection and automated lighting adjustments enhance security, while a user-friendly web interface simplifies issue identification and troubleshooting. This system is expected to improve energy efficiency, environmental sustainability, and public safety. Additionally, a placement strategy based on a predefined scheme is necessary for effective implementation.